Lithium ion battery

By using Li3PO4 as a positive electrode active material and maintaining a high volume fraction of CAE in the solvent, the lithium-ion battery electrolyte effectively reduces storage property deterioration, maintaining improved input/output characteristics.

JP2025066318AActive Publication Date: 2025-04-23TOYOTA JIDOSHA KK
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023175817
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-11
Publication Date
2025-04-23
Estimated Expiration
2043-10-11

AI Technical Summary

Technical Problem

The use of carboxylic acid esters (CAEs) in lithium-ion battery electrolytes improves input/output characteristics but tends to reduce storage properties, making it difficult to increase the volume fraction of CAE without deteriorating storage characteristics.

Method used

Incorporating Li3PO4 as a positive electrode active material and using a solvent with a volume fraction of CAE at 20% or more, which forms a stable protective coating on the positive electrode active material, reducing oxidative decomposition of CAE and thereby minimizing the deterioration of storage characteristics.

Benefits of technology

The proposed configuration reduces the deterioration of storage characteristics by stabilizing the positive electrode and minimizing CAE decomposition, thereby maintaining the improved input/output characteristics while enhancing storage properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025066318000001_ABST
    Figure 2025066318000001_ABST
Patent Text Reader

Abstract

To reduce the deterioration of storage properties associated with the use of carboxylic acid esters.SOLUTION: A lithium ion battery includes a positive electrode, a negative electrode, and an electrolyte. The positive electrode includes a positive electrode mixture. The positive electrode mixture includes a positive electrode active material and Li3PO4. The electrolyte includes a lithium salt and a solvent. The solvent includes a carboxylic acid ester in a volume fraction of 20% or more.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to lithium-ion batteries. [Background technology]

[0002] Japanese Patent Application Laid-Open No. 2019-050155 (Patent Document 1) discloses an electrolyte solution that may contain esters. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2019-050155 A Summary of the Invention [Problem to be solved by the invention]

[0004] In general, the electrolyte of a lithium ion battery (hereinafter may be abbreviated as "battery") contains carbonate as a solvent. Carboxylic acid ester (CAE) may have a lower viscosity than carbonate. By replacing a part of carbonate with CAE, for example, improvement of input / output characteristics is expected. However, the use of CAE tends to deteriorate storage characteristics. Therefore, it has been difficult to increase the volume fraction of CAE in the solvent.

[0005] An object of the present disclosure is to mitigate the loss of storage properties associated with the use of carboxylic acid esters. [Means for solving the problem]

[0006] 1. A lithium ion battery according to one aspect of the present disclosure has the following configuration. The lithium ion battery includes a positive electrode, a negative electrode, and an electrolyte. The positive electrode includes a positive electrode mixture. The positive electrode mixture includes a positive electrode active material and Li3PO4. The electrolyte includes a lithium salt and a solvent. The solvent includes a carboxylate ester in a volume fraction of 20% or more.

[0007] Generally, the higher the volume fraction of CAE in the electrolyte, the lower the storage characteristics tend to be. CAE tends to have a lower oxidative decomposition potential than carbonate. It is believed that the increase in the amount of CAE decomposed in the positive electrode promotes the deterioration of storage characteristics.

[0008] According to the new findings of the present disclosure, by adding Li3PO4 to the positive electrode composite and by setting the volume fraction of CAE in the electrolyte to 20% or more, it is expected that the deterioration of storage characteristics due to the increase in CAE is mitigated. By setting the amount of CAE that is easily oxidatively decomposed to a specific amount or more, the reaction between CAE and Li3PO4 can be promoted on the surface of the positive electrode active material. It is believed that this reaction quickly forms a stable protective film. After the protective film is formed, it is expected that the oxidative decomposition of CAE is mitigated. In other words, it is expected that the deterioration of storage characteristics is mitigated.

[0009] 2. The lithium ion battery described in "1" above may have, for example, the following configuration: When fully charged, the positive electrode has a voltage of 4.5 V (vs. Li / Li + ) is configured to have the following potential:

[0010] Conventionally, the protective coating made of Li3PO4 is 4.5V (vs. Li / Li + ) is formed at a high potential exceeding 4.5V (vs. Li / Li) according to the new findings of the present disclosure. + At a positive electrode potential of 0.1 V or less, a stable protective film can be formed. This is expected to further reduce the deterioration of storage characteristics.

[0011] 3. The lithium ion battery according to the above item "1" or "2" may have, for example, the following configuration: The carboxylic acid ester is at least one selected from the group consisting of methyl propionate and methyl acetate.

[0012] 4. The lithium ion battery according to any one of the above items "1" to "3" may have the following configuration, for example: The mass fraction of Li3PO4 with respect to the total of the positive electrode active material and Li3PO4 is 1 to 10%. The solvent contains a carboxylate ester in a volume fraction of 20 to 70%.

[0013] 5. A lithium ion battery according to an aspect of the present disclosure may have the following configuration. The lithium ion battery includes a positive electrode, a negative electrode, and an electrolyte. The positive electrode includes a positive electrode mixture. The positive electrode mixture includes a positive electrode active material and Li3PO4. The mass fraction of Li3PO4 with respect to the total of the positive electrode active material and Li3PO4 is 1 to 10%. The electrolyte includes a lithium salt and a solvent. The solvent includes a carboxylic acid ester with a volume fraction of 20 to 70%. When the positive electrode is fully charged, the positive electrode is charged to 4.5 V (vs. Li / Li + ) is configured to have the following potential:

[0014] Hereinafter, an embodiment of the present disclosure (hereinafter, may be abbreviated as "the present embodiment") will be described. However, the present embodiment does not limit the technical scope of the present disclosure. The present embodiment is illustrative in all respects. The present embodiment is non-restrictive. The technical scope of the present disclosure includes all modifications within the meaning and scope equivalent to the description of the claims. For example, it is also originally intended that any configuration may be extracted from the present embodiment and arbitrarily combined. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a conceptual diagram showing an example of a lithium ion battery according to an embodiment of the present invention. [Diagram 2] Table 1 shows the experimental results. [Diagram 3] 1 is a graph showing the relationship between the volume fraction of CAE and the remaining capacity. [Figure 4] 1 is a graph showing the relationship between the volume fraction of CAE and the amount of gas generated. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] <Key terms> The stoichiometric composition formula shows a representative example of a compound. The compound may have a non-stoichiometric composition. For example, "Li3PO4" is not limited to a compound having a substance amount ratio (molar ratio) of "Li / P / O=3 / 1 / 4". "Li3PO4" indicates a compound containing Li, P and O in any molar ratio unless otherwise specified. For example, the compound may be doped with a trace element. A part of Li, P and O may be replaced with another element.

[0017] "Carboxylic acid ester (CAE)" refers to a compound derived from the condensation of a carboxylic acid with an alcohol. Carboxylic acid esters are distinguished from carbonates.

[0018] "Fully charging" refers to charging until the reactive active materials return to the state they were in before they were discharged. Fully charging can also be referred to as "full charging," "100% charge level," or "100% state of charge (SOC)."

[0019] "V (vs. Li / Li + ) indicates the potential relative to lithium (Li) metal (zero).

[0020] Numerical ranges such as "m to n%" include upper and lower limits unless otherwise specified. That is, "m to n%" indicates a numerical range of "m% or more and n% or less". "m% or more and n% or less" includes "more than m% and less than n%". "More than" and "less than" are represented by an inequality sign with an equal sign "≦". "More than" and "less than" are represented by an inequality sign without an equal sign "<". A numerical value arbitrarily selected from within the numerical range may be set as a new upper or lower limit. For example, a new numerical range may be set by arbitrarily combining a numerical value within the numerical range with a numerical value described in another part of this specification, in a table, in a figure, or the like.

[0021] <Lithium-ion battery> 1 is a conceptual diagram showing an example of a lithium ion battery in this embodiment. The battery 100 includes a power generating element 50 and an exterior body 90. The exterior body 90 is sealed. The exterior body 90 may be, for example, a metal case or a pouch made of a metal foil laminate film. The exterior body 90 houses the power generating element 50 and an electrolyte (not shown).

[0022] <Electrolyte> The electrolyte is a liquid electrolyte. The electrolyte includes a Li salt and a solvent. The Li salt is dissolved in the solvent. The concentration of the Li salt may be, for example, 0.5 to 2 mol / L or 1 to 1.5 mol / L. The Li salt may be, for example, at least one selected from the group consisting of LiPF6, LiBF4, LiClO4, LiN(SO2F)2 "LiFSI", and LiN(SO2CF3)2 "LiTFSI".

[0023] The solvent contains 20% or more CAE by volume fraction. The solvent may be, for example, 20% or more CAE by volume fraction, with the remainder being carbonate. The volume fraction of the CAE may be, for example, any of 40% or more, 50% or more, 60% or more, 70% or more, 80% or more, or 90% or more. The volume fraction of the CAE may be, for example, any of 100% or less, 90% or less, 80% or less, 70% or less, 60% or less, 50% or less, or 40% or less.

[0024] The CAE may be, for example, at least one selected from the group consisting of methyl formate (MF), methyl acetate (MA), methyl propionate (MP), and diethyl malonate (DEM). The CAE may include, for example, at least one selected from the group consisting of MP and MA.

[0025] The carbonate may include at least one selected from the group consisting of cyclic carbonates and chain carbonates. The cyclic carbonate may include at least one selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), and monofluoroethylene carbonate (FEC). The chain carbonate may include at least one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC).

[0026] The solvent may, for example, satisfy the following relationship: Va+Vb+Vc=100% 20%≦Va≦40%, 0%≦Vb≦50%, 20%≦Vc≦70% Va: Volume fraction of cyclic carbonate Vb: Volume fraction of chain carbonate Vc: Volume fraction of CAE

[0027] The electrolyte may further contain an arbitrary additive in addition to the Li salt and the solvent. The amount of additive (mass fraction relative to the entire electrolyte) may be, for example, 0.01 to 5%, or 0.1 to 1%. The additive may include, for example, vinylene carbonate (VC), LiB(C2O4)2 "LiBOB", etc.

[0028] <Power generation elements> The power generating element 50 may also be referred to as, for example, an "electrode body." The power generating element 50 includes a positive electrode 10 and a negative electrode 20. The power generating element 50 may further include a separator 30. The power generating element 50 may have any form. The power generating element 50 may be, for example, either a wound type or a laminated type.

[0029] <Positive electrode> The positive electrode 10 may be, for example, in the form of a sheet. The positive electrode 10 may include, for example, a positive electrode current collector and a positive electrode composite layer. The positive electrode current collector supports the positive electrode composite layer. The positive electrode current collector may include, for example, aluminum (Al) foil or the like. The positive electrode composite layer may be made of a positive electrode composite. The positive electrode composite includes a positive electrode active material and Li3PO4. The mass fraction of Li3PO4 with respect to the total of the positive electrode active material and Li3PO4 may be, for example, 1 to 10%. The mass fraction of Li3PO4 may be, for example, 2% or more, 3% or more, 4% or more, 5% or more, 6% or more, 7% or more, 8% or more, or 9% or more. The mass fraction of Li3PO4 may be, for example, 9% or less, 8% or less, 7% or less, 6% or less, 5% or less, 4% or less, 3% or less, or 2% or less.

[0030] The positive electrode active material may be, for example, a particle group (powder). The D50 of the positive electrode active material may be, for example, 1 to 30 μm or 5 to 15 μm. "D50" indicates a particle diameter at which the cumulative distribution is 50% in a volume-based particle size distribution (cumulative distribution). The particle size distribution can be measured by a laser diffraction method. The positive electrode active material may contain any component. The positive electrode active material may contain, for example, at least one selected from the group consisting of LiCoO2, LiNiO2, LiMnO2, LiMn2O4, Li(NiCoMn)O2, Li(NiCoAl)O2, and LiFePO4. For example, "(NiCoMn)" in "Li(NiCoMn)O2" indicates that the sum of the composition ratios in parentheses is 1. As long as the sum is 1, the amount of each component is arbitrary. Li(NiCoMn)O2 is, for example, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.8 Co 0.1 Mn 0.1 It may contain O2, etc. 1 / 3 Co 1 / 3 Mn 1 / 3 O2 may be abbreviated as "NCM."

[0031] When the battery 100 is fully charged, the positive electrode 10 is 4.5V (vs. Li / Li + The positive electrode potential when fully charged may be, for example, 4.4 V (vs. Li / Li + ) or less, or 4.3V (vs. Li / Li + The positive electrode potential at full charge is, for example, 4.2 V (vs. Li / Li + ) or higher, or 4.3V (vs. Li / Li + ) Any of the above is acceptable.

[0032] The positive electrode mixture may further include, for example, a conductive material and a binder in addition to the positive electrode active material and Li3PO4. The conductive material may include, for example, at least one selected from the group consisting of carbon black (CB), vapor-grown carbon fiber, carbon nanotubes, and graphene flakes. The amount of the conductive material may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the positive electrode active material.

[0033] The binder may include at least one selected from the group consisting of polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP), and polyacrylic acid (PAA). The amount of the binder may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the positive electrode active material.

[0034] <Negative electrode> The negative electrode 20 may be, for example, in the form of a sheet. The negative electrode 20 may include, for example, a negative electrode current collector and a negative electrode composite layer. The negative electrode current collector supports the negative electrode composite layer. The negative electrode current collector may include, for example, copper (Cu) foil or the like. The negative electrode composite layer may be made of a negative electrode composite. The negative electrode composite includes a negative electrode active material. The negative electrode active material may be, for example, a particle group. The D50 of the negative electrode active material may be, for example, 1 to 30 μm or 5 to 15 μm. The negative electrode active material may include any component. The negative electrode active material may include, for example, at least one selected from the group consisting of natural graphite, artificial graphite, soft carbon, hard carbon, silicon (Si), silicon oxide (SiO), Si-based alloy, Si-C composite material, tin, tin oxide, and lithium titanate. The "Si-C composite material" may include, for example, composite particles. The composite particles may include, for example, porous carbon particles, and Si particles may be supported within the pores of the porous carbon particles.

[0035] The negative electrode mixture may further contain, for example, a binder in addition to the negative electrode active material. The binder may contain, for example, at least one selected from the group consisting of styrene butadiene rubber (SBR), carboxymethyl cellulose (CMC), polyimide (PI), and polyamide imide (PAI). The amount of the binder may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the negative electrode active material.

[0036] <separator> The separator 30 is disposed between the positive electrode 10 and the negative electrode 20. The separator 30 separates the positive electrode 10 from the negative electrode 20. The separator 30 may include, for example, a porous film or the like. The separator 30 may have, for example, a Gurley value of 200 to 400 seconds / 100 mL. The "Gurley value" can be measured by a Gurley test method. The separator 30 may have, for example, a multi-layer structure. The multi-layer structure may be formed by, for example, laminating a polypropylene (PP) layer, a polyethylene (PE) layer, and a PP layer in this order. EXAMPLES

[0037] <Preparation of test cell> Figure 2 is Table 1 showing the experimental results. Cells (lithium ion batteries) No. 1 to No. 27 were fabricated according to the following procedure.

[0038] Preparation of the positive electrode The following materials were prepared: Cathode active material: NCM Conductive material: CB Binder: PVdF Dispersion medium: N-methyl-2-pyrrolidone (NMP) Positive electrode collector: Aluminum foil

[0039] A slurry was prepared by mixing NCM, CB, Li3PO4, PVdF, and NMP. The solid content ratio was "NCM / CB / PVdF = 87 / 10 / 3 (mass ratio)". The amount (mass fraction) of Li3PO4 was 5% with respect to the total of NCM and Li3PO4. The slurry was applied to the surface of a positive electrode current collector to form a positive electrode composite layer. The positive electrode composite layer was compressed to produce a positive electrode.

[0040] Preparation of the negative electrode The following materials were prepared: Negative electrode active material: natural graphite (D50=20μm) Binder: SBR, CMC Dispersion medium: water Negative electrode current collector: Cu foil

[0041] A slurry was prepared by mixing graphite, CMC, SBR, and water. The solid content ratio was graphite / CMC / SBR=98 / 1 / 1 (mass ratio). The slurry was applied to the surface of the negative electrode current collector to form a negative electrode composite layer. The basis weight of the negative electrode composite layer was adjusted so that the ratio of the negative electrode capacity to the positive electrode capacity was 1.1. The negative electrode composite layer was compressed to produce a negative electrode.

[0042] assembly The following materials were prepared: Separator: Three-layer structure (PP layer / PE layer / PP layer), Gurley value = 300 seconds / 100 mL Exterior: Pouch made of aluminum laminated film Electrolyte: LiPF6 (concentration = 1 mol / L), solvent composition (see Figure 2)

[0043] A power generating element was formed by stacking the positive electrode, the separator, and the negative electrode. The power generating element was housed in an exterior body. An electrolyte solution was injected into the exterior body. After the electrolyte solution was injected, the exterior body was sealed to prepare a cell.

[0044] Activation Treatment The following cycle of constant current charging and discharging was repeated three times in a thermostatic chamber (set temperature: 25°C). "C" is the symbol that represents the time rate of current. A current of 1C will drain the rated capacity of the cell in one hour. Constant current charging: Current = 0.1C, Cutoff voltage = 4.3V Constant current discharge: Current = 0.3C, Cut voltage = 3V

[0045] Capacity measurement The initial capacity (initial discharge capacity) was measured by the following constant current-constant voltage charging and constant current discharging. Constant current-constant voltage charging: current = 0.1C, upper limit voltage = 4.3, cut current = 0.02C Constant current discharge: Current = 0.2C, Cut voltage = 3V

[0046] <Preservation test> The initial volume of the cell was measured by the Archimedes method. The cell voltage was adjusted to 4.3V by constant current-constant voltage charging (current = 0.1C, upper limit voltage = 4.3V) in a thermostatic bath (set temperature: 25°C). After adjusting the voltage, the cell was left to stand in a thermostatic bath (set temperature: 60°C) for 100 days. After 100 days, the cell was discharged in a thermostatic bath (set temperature: 25°C) by constant current discharge (current = 0.2C, cut voltage = 3V) to measure the remaining capacity. The value in the "Remaining capacity" item in Figure 2 (Table 1) is the percentage of the remaining capacity relative to the initial capacity. It is considered that the larger the remaining capacity, the less the deterioration of storage characteristics is.

[0047] After discharge, the volume of the cell after storage was measured by Archimedes' method. The amount of gas generated was measured by subtracting the initial volume from the volume after storage. It is considered that the smaller the amount of gas generated, the less deterioration of storage characteristics is.

[0048] <Result> In Figure 2 (Table 1), cells that satisfy the following conditions (A) and (B) tend to have little deterioration in storage characteristics. In the table, the "No." of cells that satisfy the following conditions (A) and (B) is marked with an "*", such as "No.*16". (A) The volume fraction of CAE (MP, MA) in the electrolyte (solvent) is 20% or more. (B) The positive electrode mixture includes a positive electrode active material and Li3PO4.

[0049] FIG. 3 is a graph showing the relationship between the volume fraction of CAE and the remaining capacity. When Li3PO4 is not added to the positive electrode composite, the remaining capacity tends to decrease monotonically with an increase in the volume fraction of CAE. FIG. 4 is a graph showing the relationship between the volume fraction of CAE and the amount of gas generated. When Li3PO4 is not added to the positive electrode composite, the amount of gas generated tends to increase monotonically with an increase in the volume fraction of CAE.

[0050] In Figures 3 and 4, when Li3PO4 is added to the positive electrode composite, the deterioration behavior of the storage characteristics changes at a volume fraction of 20%. That is, at a volume fraction of 20%, the deterioration behavior of the storage characteristics is reversed once, and then tends to become gentler. It is considered that the deterioration of the storage characteristics is reduced at a volume fraction of 20% or more.

[0051] In Figure 2 (Table 1), the value in the "positive electrode potential" column indicates the positive electrode potential at full charge. From the results of No. 1, No. 12, No. 25, No. 26, and No. 27, when the solvent is carbonate (EC / EMC=30 / 70), the positive electrode potential is 4.5 V (vs. Li / Li + ), the effect of adding Li3PO4 tends to be significant.

[0052] From the results of No. 7, No. *18, No. *23, and No. *24, when the solvent contains CAE (MP), the positive electrode potential is 4.5 V (vs. Li / Li + ) or less, the effect of adding Li3PO4 tends to be significant. [Explanation of symbols]

[0053] 10 Positive electrode, 20 Negative electrode, 30 Separator, 50 Power generating element, 90 Exterior body, 100 Battery (lithium ion battery).

Claims

1. A positive electrode, a negative electrode, and an electrolyte solution, The positive electrode includes a positive electrode mixture, The positive electrode mixture is a positive electrode active material and Li 3 P.O. 4 Including, The electrolyte solution includes a lithium salt and a solvent, and The solvent contains a carboxylic acid ester in a volume fraction of 20% or more. Lithium-ion battery.

2. When fully charged, the positive electrode is 4.5 V (vs. Li / Li + ) configured to have the following electrical potential:

2. The lithium ion battery of claim 1.

3. The carboxylic acid ester is at least one selected from the group consisting of methyl propionate and methyl acetate. The lithium ion battery according to claim 1 or 2.

4. The positive electrode active material and Li 3 P.O. 4 Li for the sum of 3 P.O. 4 is from 1 to 10% by mass, and The solvent contains 20 to 70% by volume of the carboxylic acid ester. The lithium ion battery according to claim 1 or 2.

5. A positive electrode, a negative electrode, and an electrolyte solution, The positive electrode includes a positive electrode mixture, The positive electrode mixture is a positive electrode active material and Li 3 P.O. 4 Including, The positive electrode active material and Li 3 P.O. 4 Li for the sum of 3 P.O. 4 is from 1 to 10% by mass, The electrolyte solution includes a lithium salt and a solvent, The solvent comprises 20 to 70% by volume of a carboxylic acid ester; and When fully charged, the positive electrode is 4.5 V (vs. Li / Li + ) configured to have the following electrical potential: Lithium-ion battery.

Citation Information

Patent Citations

  • Nonaqueous electrolytic solution for secondary battery, and nonaqueous electrolytic solution secondary battery using the same

    JP2008140760A

  • Nonaqueous electrolyte secondary battery

    JP2008243810A

  • Lithium ion secondary battery

    JP2018101493A

  • Positive electrode for nonaqueous electrolyte secondary batteries, and nonaqueous electrolyte secondary battery

    WO2016084346A1

  • Non-aqueous electrolyte secondary cell

    WO2016084357A1